Abdulla Qodiriy ve Özbek romanının doğuşu - Merhan, Aziz (Grafiker Yayıncılık, 2008)
Uzbek novelist Abdulla Qodiriy (1894-1938) left his mark upon a period with the works he wrote. Apart from countless presses, he left behind a play, tens of stories and two novels in his literary life that he began with poem. He became the founder of the modern novel writing in Uzbek literature particularly thanks to his historical novels
Literaturverz. S. 262 - 272
Keywords: Ķodirij; Abdulla; Abdulla Qodiriy; 1894-1938; Uzbek literature; Uzbek novel; Usbekisch; Literatur